A Linguistic Landscape Study of English in Yogyakarta: Its Representation of Power in Commercial Boards - Dewianti Khazanah; Hadi Sampurna; Reni Kusumaningputri; Riskia Setiarini; Supiastutik Supiastutik (ELLITE, 2021)
This research explores how English is used in the expanding circle: tourism areas in Yogyakarta, Indonesia. Although Bahasa Indonesia is the official language used, this does not mean that other languages will have a little share in the linguistic landscape. The total data used were 519 signboards which were analyzed qualitatively and quantitatively. This research found that in monolingual boards, the use of English was 23.7%, and Indonesian was 73.5%. The magnitude of the use of English, which is close to as salient as the use of Bahasa Indonesia, is particularly shown on the bilingual and multilingual signboards. This study highlights discussion on the representation of power of English in the investigated signboards, which was shown from the number of appearance and combination of English and other languages in the signboards. It is revealed that English is expressed not only for informative reasons but also for symbolic reasons such as indexing sophistication, cosmopolitanism, and fashionable appearance.